Diabetes Distress During COVID-19: Three Brief ‘Snapshot’ Surveys of Adults With Diabetes Calling the Australian National Diabetes Services Scheme Helpline - Holloway, Edith E.; Hendrieckx, Christel; Company, George; Skinner, Timothy C.; Speight, Jane (Frontiers in Clinical Diabetes and Healthcare, 2021)
The aim of this study was to take ‘snapshots’ of how people with diabetes are feeling emotionally during the coronavirus disease 2019 (COVID-19) pandemic. Three ‘snapshot’ surveys were conducted during May 2020, August 2020 and April 2021, each over a two-week period. Adults (>18 years) with diabetes calling the Australian Government’s National Diabetes Services Scheme Helpline (NDSS) were invited to participate. Those who accepted were asked three questions sourced/adapted from the Problem Areas in Diabetes scale. Responses were recorded on a 5-point scale (0=’not a problem’, 4=’serious problem’). In total, 1,278 surveys were completed over the three ‘snapshots’ (1st N=449; 2nd N=414; 3rd N=415). Participants were aged (median[IQR]) 62[47,72] years, 56% were women, and 57% had type 2 diabetes. At the 3rd ‘snapshot’. Feeling at least moderately ‘burned out’ by the constant effort needed to manage diabetes is salient, and consistently experienced by adults with diabetes calling the NDSS Helpline at three timepoints during the coronavirus pandemic. Those who participated in the 3rd ‘snapshot’ survey were less likely to report that feeling ‘alone with their diabetes’ or ‘worrying about their diabetes because of the COVID-19 pandemic’ were moderate or serious problems for them. Except for younger adults, findings indicate that the easing of restrictions may mitigate some of the effects of the pandemic on diabetes-specific emotional problems. Prospective data are needed to improve our understanding of the emotional impact of COVID-19 on people with diabetes and to inform when and how to target support for those who need it most.